Modifiable risk factors for hypertensive disorders in pregnancy - Mei-Wei Chang; Alai Tan; Joshua M. Smyth; Duane T. Wegener (Critical Public Health)
Hypertensive disorders in pregnancy (HDPs) are the leading causes of maternal mortality and morbidity. This study explored whether micronutrient intake and psychological distress were associated with HDPs. Micronutrients include folate and vitamin B12. Psychological distress refers to perceived stress, prenatal distress, and prenatal depression. HDPs were defined as systolic blood pressure (BP) ≥130 mmHg or diastolic BP ≥80 mmHg. Data were collected at ≤17 weeks gestation (T1), 25–27 weeks gestation (T2), and 35–37 weeks gestation (T3). T-tests comparing those with and without HDP were performed to explore the associations. Results showed that folate and vitamin B12 were associated with HDPs at T1 and T2 (T1: d = –0.41, d = –0.52; T2: d = –0.43, d = –0.24). Psychological distress was positively associated with HDPs, but associations varied between timepoints and by measure – prenatal distress at all times (T1: d = 0.26; T2: d = 0.54, T3: d = 0.40), perceived stress at T3 (d = 0.34), and prenatal depression at T2 and T3 (T2, d = 0.47; T3: d = 0.68). In summary, micronutrient intake and psychological distress are associated with HDPs but varied by construct and across gestational age.